Implementation of Balance of Control and Flexibility of Government Budget using Management Control System - Sitanggang, Ariano (E-Jurnal Akuntansi, 2025)
This study aims to analyze the application of control balance and budget flexibility in the XYZ Government Work Unit using the four levers of control framework. The research was conducted using the case study method. XYZ Work Unit (Satker) is one of the units implementing tasks and functions in the field of government internal audit. Primary data was obtained from semi-structured interviews with Satker XYZ management. Secondary data is obtained from reviewing planning, implementation and performance reporting documents at Satker XYZ. The research resulted in the application of control balance and budget flexibility in the XYZ Government Work Unit can be supported by communicating the beliefs system, sanctioning conformity with the boundary system, preparing detailed budget diagnostic controls and interactive controls in predicting the need for budget changes. Keywords: Government Budgeting; Budget Control; Budget Flexibility.